Tren dan Hubungan Antara Keseimbangan Kehidupan Kerja dan Kinerja Karyawan: Analisis Scientometrik - Agnes Nunung Ariasari; Heru Kurnianto Tjahjono (Society, 2024)
This study employs a scientometric approach to analyze trends and relationships between work-life balance (WLB) and employee performance. The data were sourced from the Scopus database using the keywords “Work-Life Balance” AND “Employee Performance,” resulting in the analysis of 449 articles. The study examines research trends, collaboration networks, topic mapping, and the evolution of research themes from 1994 to 2023. Bibliometric mapping and data visualization were conducted using VOSviewer, RStudio, and CiteSpace. The findings reveal that WLB is a critical factor in employee satisfaction and engagement, directly contributing to improved organizational performance. The COVID-19 pandemic has accelerated the adoption of remote work models, underscoring the significance of flexible working arrangements and effective HR management in achieving optimal WLB. Work autonomy and WLB are shown to have a substantial impact on job satisfaction and employee performance. A comprehensive strategy that integrates organizational support with individual well-being is essential to fostering a productive and satisfied workforce. This research provides a robust theoretical foundation for HR models. Practically, organizations should implement strategies that prioritize both organizational support and employee well-being to enhance workforce productivity. The telecommuting models and flexible arrangements that gained prominence during the COVID-19 pandemic should be permanently embedded into organizational policies. Future research should explore the relationship between WLB and various dimensions of employee performance within a broader context, taking into account cultural and industry-specific variations.